REPRESENTASI NILAI MORAL FILM “SIKSA KUBUR” KARYA JOKO ANWAR KAJIAN EKSPLORATIF - Afriany, Fany (Jurnal Pena Indonesia, 2024)
Film is a medium that is often used to convey moral messages to its audience. One of the controversialmovies in the context of moral values is “Siksa Kubur” by Joko Anwar. This film is based on achildhood incident experienced by the main character Sita and Adil who had a trauma over the deathof his parents due to a suicide bombing carried out by a man who claimed to record the sound of gravetorment, since then Sita has a great distrust of religion. This study aims to analyze the moral valuescontained in the film. The qualitative analysis method is used to identify and evaluate the moralmessages conveyed through narration, character, and conflict in the movie. The results showed that“Siksa Kubur” raised complex themes, one of which was the element of morality. This research isexpected to provide a deeper understanding of how movies can influence the perception and moralattitudes of their audiences, as well as their relevance in the context of Indonesian culture and society.